EFEKTIFITAS KOMBINASI MINT DAN CAIRAN DENGAN NEBULIZER PADA PENANGAN BATUK ASMA BRONCHIALE - Farida Anwari; Melawati Olevianingrum; Umi Fatmawati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2019)
Farida Anwari 1), Melawati Olevianingrum 2), Umi Fatmawati 3) (Times New Roman, 11pt, bold)STIKES RS. Anwar Medika Sidoarjo, Jl. Bypass Krian KM 33 Balongbendo, Sidoarjofaridamph@gmail.com Hp. 08123248102 ABSTRACT Polluted air and contaminated seeds can cause various lung diseases, one of which is indicated by cough changes. Coughing into body shape, occurs as a response from the body to irritation in the throat due to mucus, dust, smoke and air outside the body. Nebulizer is an alternative tool to relieve the cough response to the presence of mucus which is an inflammatory reaction due to infection in the respiratory tract. Mint oil in the form of extracts has a variety of esters, especially menthyl acetate and monoterpenes which produce a distinctive aroma that is beneficial for breathing. The aim of the study was to examine the effect of adding mint oil as a result of distillation on the liquid with the nebulizer in cough handling. This study was a pre-experimental study with nonrandomized design pre test and post test with control group design which was used to determine the effect of the addition of mint oil as a result of distillation on the liquid with nebulizer to reduce the coughing status of the patient which included (cough frequency, onset of inflammation, wheezing, and ease of expectoration of phlegm). The results showed that the cough frequency status is known to have decreased from 44.4% of patients to 23.5% of patients. Similarly, the status of inflammation decreased from 41.7% to 21.7%; wheezing status which was originally 58.3% decreased to 39.1%; easy expectoration status also shows that mint oil can reduce the level of difficulty of phlegm to go out to 13% from 36.1%.